Managing Access Rights for the Repositories of U.Porto - Cristina Ribeiro (2012)
Digital repositories are replacing traditional archives, and their functions largely exceed those of their ancestors. In a higher education institution, wheremultiple activities take place motivated by its teaching, research, community engagement and cultural missions, repositories may become endowed with aspectrum of functionalities that range from the support for teaching resources, the registry of academic publication, the management of research data, thepreservation of heritage materials and the dissemination of timely news.In this paper we are looking at the repository structure of U.Porto from the point of view of access rights and access restrictions. The experience at U.Portohas shown that an institutional repository does require considerable effort in the identification of the materials to be incorporated, and that a substantial part ofthat effort has to be devoted to the management of the access conditions.We consider a set of case studies from U.Porto documents and analyze the processes required to make them available. The cases cover scientific papers,research data and administrative documents, and are just a sample of the many situations the university is facing in its mission of preserving the institutionalmemory and making resources available to a large audience in and outside the university.